E–availability of financial documents for US' counties. (21st January 2014) - Baker, David L.; Jr., C.E. Tapie Rohm
The electronic availability (e–availability) of financial documents helps stakeholders evaluate government performance, solvency, and sustainability. This study reviews the e–availability of financial documents (EFDs) from county websites in the USA. It facilitates the development of a more transparent and accountable county government. While some baseline research exists for EFDs for cities, little is known regarding EFDs for counties. The study extends research about the types of local governments where EFDs exists and sheds light on a literature gap concerning counties. It reviews public sector incentives for EFDs, related best practices, and essential county financial documents. Using content analysis, data collected from 100 counties are reviewed to establish a baseline for county EFDs. After analysis, the paper concludes with a review of stakeholder implications and study limitations. Furthermore, it offers recommendations for future research regarding EFDs to enhance transparency and accountability while earning greater trust among county stakeholders.